A Comparative Study of C, C++, C# and Java Programming Languages: Underpinning Structure Equation Modeling, Data Structures and Algorithm - Mutongwa, Sanja Michael; Abeka, Silvance (Journal of Scientific and Engineering Research, 2019)
Equation Modeling technique has not been fully utilized in the field of Software analysis in handling complex data analysis and modeling on programming languages by a number of researches globally and specifically by Universities in East Africa, in a nut shell; secures programming practices and daily life application is still wanting. We present a comparative study of C, C++, C#, and Java Programming languages: Underpinning Structure Equation Modeling; with respect to: Runtime tests, compilation, Model comparison, Latent Curve model, rate of change over time, Runtime tests, sorting criteria and compilation. Findings indicated that Java was: (Var_Inter =0.81 and Var_slop =0.02). The overall model fit for Java had (RMR =0.000, CFI = 9.88, TLI = 1.0, and NFI = 0.99), while that of C-language was poorly fitted, its Latent Curve model results: (Var-Inter =0.41 and Var_Slop =0.31) hence not significant. Rule of thumb utilized was excellent; Java was rated higher in terms of Runtime tests, same applied to sorting criteria; Merge sort, applicabilication and compilation, While C was the least. C++ gave close results to C, Comparatively C# had better finding. On sorting criteria, Java indicated a more coherent than a C++ and C, but closer to C#, Java was rated as more simplified, Java applications are more than the 3 languages. Study recommends further investigation on C and C++, all the same there is need to carry out research on more than four languages and to use a larger sample size.
Keywords: Structure Equation Modeling; C; C++; C#; Java Programming